Features of the influence of practicing various sports on the organs of the gastrointestinal tract - V. A. Akhmedov; D. A. Gavrilenko (Лечащий Врач)
Every person who is actively involved in sports has at least once encountered problems from the gastrointestinal tract during competition or training. The physical condition of the athlete is one of the key factors in achieving the set goals and somatic disorders can interfere with the desired results. Three groups of reasons for the development of gastrointestinal symptoms in athletes were identified: physiological, mechanical, and associated with nutrition. Timely identification and correction of violations during physical activity provides an increase in the quality of life of athletes and maintenance of high results. The rapid increase in the number of people actively involved in sports has led to the fact that the function of medical supervision and giving recommendations on rational nutrition while playing sports becomes the responsibility of the work of primary care physicians. The study of the effect of physical activity on organs and systems becomes very important. The review article presents data on the etiology and mechanisms of the formation of gastrointestinal symptoms in athletes during training and considers recommendations for preventing their occurrence.